Effectiveness of montelukast in childhood asthma: a prospective observational study - Gangdev, Krutika; Jain, Hemant; Luhadia, Atul (International Journal of Contemporary Pediatrics, 2021)
Background: Asthma is characterized by hyperresponsiveness of airways to various stimuli, manifested by widespread narrowing of airways causing paroxysmal dyspnoea, wheezing or cough. Most asthma medications are inhalational and compliance is difficult. So, development of an orally active and once daily drug with additional bronchodilator properties would lead to a major advance for managing young patients with asthma. Methods: Children between 6-18 years with not well controlled asthma on daily controller therapy were enrolled. Their personal data and history regarding the duration of asthma symptoms, frequency and severity of exacerbations was noted. Diagnosis and grading of severity of asthma was confirmed by spirometry. Then subjects were started on montelukast as add on to their daily controller therapy and were reassessed at 4, 8 and 12 weeks by clinical symptoms and PEFR. The change in frequency of symptoms and PEFR at the end of 12 weeks gave the outcome of efficacy of montelukast. Side effects of montelukast were also assessed. Results: Among total 64 subjects, at 4 weeks, 52 improved to well-controlled asthma. The remaining 12 did not improve, so required an increase in dose of their daily controller medication. Out of those 12 subjects, 10 subjects improved to well-controlled asthma at 8 weeks and 2 subjects still did not improve, so, their inhaled corticosteroids (ICS) dose was further increased. All 64 subjects showed improvement at 12 weeks. No serious side effects were observed. Conclusions: 81.25% subjects showed improvement at the 1st follow up itself and no serious complications were observed. So, it can be suggested that montelukast is a safe drug.